2012
DOI: 10.1073/pnas.1200841109
|View full text |Cite
|
Sign up to set email alerts
|

Force of infection is key to understanding the epidemiology ofPlasmodium falciparummalaria in Papua New Guinean children

Abstract: Genotyping Plasmodium falciparum parasites in longitudinal studies provides a robust approach to estimating force of infection (FOI) in the presence of superinfections. The molecular parameter mol FOI, defined as the number of new P. falciparum clones acquired over time, describes basic malaria epidemiology and is suitable for measuring outcomes of interventions. This study was designed to test whether mol FOI influenced the risk of clinical malaria episodes and how far mol FOI reflected environmental determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
154
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
2
2
2

Relationship

2
4

Authors

Journals

citations
Cited by 111 publications
(166 citation statements)
references
References 47 publications
10
154
1
Order By: Relevance
“…Heterogeneity in P. falciparum transmission intensity exists, even within small geographical areas, and this may lead to differences in malaria exposure (32). In this study, we used a novel molecular marker of exposure in the cohort, mol FOI, and examined its relationship to antibody levels and associations with malaria risk.…”
Section: Figmentioning
confidence: 99%
See 4 more Smart Citations
“…Heterogeneity in P. falciparum transmission intensity exists, even within small geographical areas, and this may lead to differences in malaria exposure (32). In this study, we used a novel molecular marker of exposure in the cohort, mol FOI, and examined its relationship to antibody levels and associations with malaria risk.…”
Section: Figmentioning
confidence: 99%
“…High polymorphism of this marker was observed in this study population, with 52 different MSP2 genotypes identified (47). A new infection was defined as any MSP2 genotype detected in a given 8-week interval that was not detected during the previous interval, and the number of infections with new genotypes was calculated for each individual (32). Genotyping was undertaken on blood samples collected during both the morbidity surveillance and the 8 periods of weekly active surveillance.…”
Section: Study Populationmentioning
confidence: 99%
See 3 more Smart Citations